2005
DOI: 10.2113/11.4.371
|View full text |Cite
|
Sign up to set email alerts
|

Using Tracer Tests to Assess Natural Attenuation of Contaminants along a Channelized Coastal Plain Stream

Abstract: Tracer tests have been widely used in studies of solute transport, gas exchange, and nutrient cycling in streams. However, the use of tracer tests to assess natural attenuation of ground-water-derived contaminants in streams, particularly from point sources, has been limited. We used tracer tests in conjunction with stream gauging and contaminant analyses to study the fate of trichloroethene (TCE) and technetium-99 ( 99 Tc), which seep from industrial contaminant plumes into a channelized, first-order stream i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 52 publications
2
17
0
Order By: Relevance
“…This is the likely explanation for the very low concentrations of the TCE sampled in springs along the Little Bayou Creek (see Fig. A-1 where Little Bayou Creek has cut deeply into the Metropolis Formation, almost reaching the RGA), as reported by Fryar, et al 2000;Mukherjee, et al 2005;and LaSage, et.al. 2008a and b.…”
Section: Geological Datasupporting
confidence: 57%
See 1 more Smart Citation
“…This is the likely explanation for the very low concentrations of the TCE sampled in springs along the Little Bayou Creek (see Fig. A-1 where Little Bayou Creek has cut deeply into the Metropolis Formation, almost reaching the RGA), as reported by Fryar, et al 2000;Mukherjee, et al 2005;and LaSage, et.al. 2008a and b.…”
Section: Geological Datasupporting
confidence: 57%
“…The general geology is illustrated in the cross-section presented as Fig hence do not present continuing concerns regarding the surface water (Fryar, et al 2000;Mukherjee, et al 2005;LaSage, et al 2008a and b). Further, field work in the area north of the PGDP facility to the Ohio River have found no indications to date of liquefaction features (or other indications of surface sediment disruption) that would suggest the area has been subjected to shallow sediment faulting or associated depressurization of groundwater in confined sediments within or above the RGA.…”
Section: Geological Datamentioning
confidence: 96%
“…The management of such contamination is complicated by difficulties in identifying point sources. Water tracers such as the xanthene dye Rhodamine WT (RWT) can be utilised in the investigation of contaminant transport in hydraulic systems to examine the transport of solutes (Broshears et al, 1996;Hibbs et al, 1998;Fox et al, 2002;Gaikowski et al, 2004;Richardson et al, 2004; Correspondence to: A. Ghadouani (anas.ghadouani@uwa.edu.au) Mukherjee et al, 2005), and thus trace contaminants back to their source (Pitt et al, 1993;Lalor and Pitt, 1999;Close et al, 2002;Pitt, 2002). Whilst information regarding time of travel and flow velocity may be determined through qualitative applications of tracers, quantitative tracing is required for more precise hydrological information such as potential contaminant transport characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The potential for turbidity to impact upon our field study was assessed by measuring a range of RWT solutions prepared using water from our field site, and no significant deviation from expected fluorescence was observed hence any possible effects of turbulence on RWT fluorescence measurements were ignored for the remainder of the study. A number of studies have also demonstrated that the use of RWT in quantitative studies may be compromised by photochemical decay of RWT over time (Smart and Laidlaw, 1977;Tai and Rathbun, 1988;Suijlen and Buyse, 1994;Upstill-Godard et al, 2001;Dierburg and C. H. Mines et al: Use of rhodamine WT as proxy for point source pollutants DeBusk, 2005) and loss of RWT due to adsorption (Smart and Laidlaw, 1977;Wilson et al, 1986;Sabatini and Austin, 1991;Shiau et al, 1993;Di Fazio and Vurro, 1994;Soerens et al, 1994;Kasnavia et al, 1999;Close et al, 2002;Keefe et al, 2004;Kung et al, 2000;Vasudevan et al, 2001;Lin et al, 2003;Pang et al, 2003;Richardson et al, 2004;Dierburg and DeBusk, 2005) but as the work described here focused on the use of RWT within a closed pipe surface water drainage network these potential losses were deemed insignificant and not re-examined. Given this range of potential compromising factors, the inconsistent nature of field results concerning RWT fate and transport (Tai and Rathbun, 1988;Jones and Jung, 1990;Suijlen and Buyse, 1994;Ptak and Schmid, 1996;Kung et al, 2000;Upstill-Godard et al, 2001;Close et al, 2002;Lin et al, 2003) is unsurprising.…”
Section: Introductionmentioning
confidence: 99%
“…The management of such contamination is complicated by difficulties in identifying point sources. Water tracers such as the xanthene dye Rhodamine WT (RWT) can be utilised in the investigation of contaminant transport in hydraulic systems to examine the transport of solutes in water bodies (Broshears et al, 1996;Hibbs et al, 1998;Fox et al, 2002;Gaikowski et al, 2004;Richardson et al, 2004;Mukherjee et al, 2005), and thus trace contaminants back to their source (Pitt et al, 1993;Lalor and Pitt, 1999; Close et al, 2002;Pitt, 2002). Whilst information regarding time of travel and flow velocity may be determined through qualitative applications of tracers, quantitative tracing is required for more precise hydrological information such as potential contaminant transport characteristics.…”
Section: Introductionmentioning
confidence: 99%